Influence of mechanical activation of fly ash in presence of polynaphthalene sulfonate superplasticizer on rheology and hydration kinetics of cement – fly ash pastes. (20th June 2019) - Mezhov, Alexander; Pott, Ursula; Stephan, Dietmar; Kovler, Konstantin
Highlights: Fly ash is milled in two modes: with PNS superplasticizer and apart of it. Presence of PNS prevents adverse agglomeration of the fly ash particles. Pastes consisting fly ash milled with PNS exhibit enhanced rheological properies. Evaluated influence of PNS and fly ash on hydration kinetics of the blended binder. Abstract: In this study fly ash was milled in three types of mills up to the same median particle size ∼6 µm. The milling was performed in presence of polynaphthalene sulfonate (PNS) superplasticizer and apart of it. It is shown that the introduction of PNS during the milling allows to prevent adverse agglomeration of the particles, while increment of the specific surface area is independent of the presence of PNS. Cement – fly ash pastes prepared with PNS introduced during the fly ash activation exhibit a reduction of the yield stress by 35%, plastic viscosity by 25% and the induction period of hydration by 30% in comparison to the paste prepared with PNS introduced with the mixing water.